Safety reporting of Essure medical device: a qualitative and quantitative assessment on the FDA manufacturer and user facility device experience database in 2018 - Zou, Chenyu; Davis, Brandy; Wigle, Patricia R.; Hincapie, Ana L.; Guo, Jeff Jianfei (Frontiers in Reproductive Health, 2023)
Background: There have been numerous cases of adverse events since the introduction of Essure medical devices for sterilization in 2002. This study analyzed the safety event reports of the Essure reported in the Manufacturer and User Facility Device Experience (MAUDE). Methods: A retrospective analysis examined the MAUDE reports between Jan-1, 2018, and Oct-31, 2018 and focused on safety reports related to the Essure device. Safety reports were categorized and analyzed by their event type, device problem, patients' symptoms and the level of harm. Of this study cohort, 10% of samples were randomly selected for quantitative analyses. Thematic analysis was conducted for reports included death cases. Results: A total of 4,994 eligible reports were analyzed. There were ten reports associated with individuals’ deaths, and the main themes of safety reports from qualitative analysis were pains, bleeding, surgery , migraine, and infection. Quantitative analysis of 500 randomly selected samples showed that 98% of adverse event reports were associated with different injuries such as surgery, pain, bleeding, hysterectomy, and menorrhagia. Additionally, more than 90% of reports were submitted by the manufacturer. Conclusion: These findings indicated several safety issues of the Essure. More meaningful pre- and post-marketing surveillance and regulation are warranted in the medical device market to ensure safety and effectiveness, including investigating complaints, promptly sharing relevant information with regulators and users, and implementing corrective actions.